Low Serum Brain-Derived Neurotrophic Factor is associated with Suicidal Ideation in Major Depressive Disorder - Khan, Maryam S. (Psychiatry Res, 2019)
The “neurotrophic hypothesis of depression” posits that low levels of brain-derived neurotrophic factor (BDNF) are associated with Major Depressive Disorder (MDD). Low levels of BDNF have also been found in individuals with suicide attempts, in MDD or other disorders, suggesting that low BDNF may also be associated with suicidality. We assessed serum BDNF in 68 physically healthy and unmedicated (for at least 6 weeks) MDD subjects, who expressed no suicidal ideation (NSI; N=40) or endorsed suicidal ideation (SI; N=28), but were not actively suicidal, and in healthy controls (HC; N=76). Serum BDNF levels were significantly lower in MDD with SI compared to NSI MDD but were not significantly correlated with total Hamilton Depression Rating Scale (HDRS-17) severity or severity on any HDRS subscale. Covarying for age, sex, body mass index, platelets, perceived stress, smoking and physical activity did not alter the significant association between BDNF and SI. SI status was not significantly different between HC and MDD. Our findings show an association between low serum BDNF and SI in individuals with less than severe and non-active suicidal intent, suggesting that the individual symptom of suicidality may extend the neurotrophic hypothesis of depression to include suicidal ideation within MDD.